A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF SMPN 25 PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Koko Silaban; Danilsyah Danilsyah; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to find out the ability of the third year students of SMPN 25 Pekanbaru in comprehending Narrative Texts. The number of population was 347 students divided into nine classes. The writer used cluster random sampling to determine the sample. The samples were 80 students. The needed data were taken from the students’ score in comprehending narrative texts. The test comprehends four narrative texts of which all has five indicators and 20 items multiple choice. The time allocation was 60 minutes. The result of the study revealed that the mean score was 71.25% which indicated that the students were in good level. The highest mean score is 95.31% (identifying references) and the lowest mean score is 44% (finding social function).Key Words: Students’ ability, Reading Comprehension, Narrative texts